(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
Administration of drugs using conventional dosage forms is sometimes unsatisfactory due to variability in systemic drug levels, incomplete absorption or poor patient compliance. This article reviews some novel drug delivery systems intended to overcome some of the above shortcomings. Emphasis is placed on controlled drug delivery systems, although mention is also made of other novel drug delivery systems not based on control release principle.